Empowering Green Healthcare Supply Chain Management Practices Challenges and Future Research - Norzianis Rezali; Mohd Helmi Ali; Fazli Idris (International Journal of Supply Chain Management, 2018)
The purpose of this paper is to explore the internal challenging factors of green healthcare supply chain management practices that contributed to the sustainable development in Malaysia. Green healthcare supply chain management practices are unique, different and more complex because of the impact on the environment and also the human health. This study thoroughly analysed, reviewed and explained each factor in detail from the various previous literature perspectives. This paper is one of the first to identify and conceptually discuss the use of green healthcare supply chain management practices that contributes to the sustainable development of healthcare industries in a single setting in a developing country. This study explored the internal challenging factors of green healthcare supply chain management practices that contributed to the sustainable development of a private hospital in Malaysia. The findings of the research will enlighten our view on green healthcare supply chain management practices. Besides, it contributes to researchers, the existing corpus of knowledge and a promise to expand the research stream on green healthcare supply chain management practices. The empirical findings will suggest to green healthcare supply chain to practitioner possible ways to obtain and maintain competitive advantages in the healthcare industries as proactive strategies that contribute to the sustainable development in Malaysia.